Number of lymph nodes sampled in SFCE/SIOP 2001 patients with Wilms tumour: Is the goal of more than six achievable?. Issue 3 (1st December 2022) - Irtan, Sabine; Coulomb‐Lhermine, Aurore; Lanz, Camille; Tabone, Marie‐Dominique; Pasqualini, Claudia; Dumont, Benoit; Thebaud, Estelle; Guellec, Isabelle; Verschuur, Arnauld
Abstract: Aim: The number of lymph nodes (LN) that should be sampled during nephrectomy for Wilms tumour (WT) remains controversial but of utmost importance for staging purposes. The aim of this French national retrospective study of patients enrolled in SIOPWT2001 trial was to analyse the number of LN sampled according to their site and to determine if the number of six asked by the International Society of Paediatric Oncology ‐ Renal Tumour Study Group (SIOP‐RTSG) UMBRELLA protocol is achievable. Methods: We reviewed the data collected on central pathology review forms from 2002 to 2014 for only unilateral WT. LN were divided whether they were clearly identified by surgeons at nephrectomy or only found by pathologists on the nephrectomy specimen. Results: A total of 539 patients (240 male/299 female) were included (458 localized/81 metastatic). Median age at surgery was 41.3 months [0–189]. The number of LN sampled was 0, 1–6, ≥7 and unknown in 69 (12.8%), 293 (54.3%), 160 (29.7%) and 17 (3.2%) cases, respectively. The number of patients with sampled LN were higher if LN were identified by both the pathologist and the surgeon ( n = 231, 42.8%) ( p = < .001). At least one invaded LN (LN+) was found in 66 patients (12.2%), more than half being found among patients having LN sampled by both pathologist and surgeon ( p < .001). The mean number of identified LN was six if no LN+ was detected on final histological analysis, while it was 11 in case of LN+ ( p < .001). Conclusions: The aim of sampling more than six LN is achievable, but only with the active collaboration of both surgeons and pathologists.